الأحاديث الواردة في تفسير التحرير والتنوير من خلال سورة آل عمران : دراسة نقدية - Nazrul Affandi bin Jani (Kulliyat Ma'arif al-Wahy wa-al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah bi-Maliziya, 2013)
The research aims to study the narrated ahadith in Shaykh Ibn 'Ashur's al-Tahrir wa al-Tanwir Book of Tafsir. The study focuses on the life of Shaykh Ibn 'Ashur and the evaluation of narrated ahadith after it have been recorded. The researcher used al-Tahrir wa al-Tanwir Book of Tafsir as its main cause was to find and identify the number of narrated ahadith, especially in Tafsir of Surah Ali 'Imran. After that, those ahadith were referred to in several books of hadith and books of Rijal in order to extract the status of mentioned ahadith and to improve some of those statuses. The research finds that Shaykh Ibn 'Ashur was among those who lived and practiced the Sunnah, and he adapted the Sunnah to develop his generation as a generation who prefers religion and knowledge, even though he lived through an era of colonisation. The study also confirmed that Shaykh Ibn 'Ashur only used narrated ahadith from the Prophet, sallallahu 'alayhi wasallam. One hundred and five ahadith found in his Tafsir of Surah Ali 'Imran.